From Grouping to Coupling: A New Perceptual Organization in Vision, Psychology, and Biology - Pinna, Baingio; Porcheddu, Daniele; Deiana, Katia (Frontiers in Psychology, 2016)
In this work, perceptual organization has been studied with the same spirit and phenomenological methods used by Gestalt psychologists. This was accomplished through new conditions that cannot be explained in terms of the classical principles of grouping. Perceptual grouping represents the way through which our visual system builds integrated elements on the basis of the maximal homogeneity among the components of the stimulus pattern. Our results demonstrated the inconsistency of organization by grouping, and more importantly, the inconsistency of the principle of similarity. On the contrary, they suggested the unique role played by the principle of dissimilarity among elements that behaves like an accent or a visual emphasis within a whole. The principle of accentuation was here considered as imparting a directional structure to the elements and to the whole object thus creating new phenomena. The salience of the resulting phenomena reveals the supremacy of dissimilarity in relation to similarity and the fact that it belongs to a further organization dynamics that we called “coupling”. In biology, coupling and its principle of accentuation are very strongly related to the disruptive camouflage. Moreover, they are source of sexual attraction. They advertise the presence and elicit species identification/communication. In human beings accentuation is needed to show ourselves to others, to understand the way we dress, choose and create clothes or invent fashion, the way we change our body accentuating several parts and hiding some others, the way we use maquillage. The existence of maquillage itself is derived from the need to accentuate something with the purpose to increase sexual attraction, to exhibit physical strength and beauty, to show or hide social status (e.g., being the king, a warrior, a priest, etc.). Last but not least, accentuation plays a basic role also in making it easier or difficult to read and understand written words.